Home-Made Micro Valve for Determining Malachite Green Dye by Flow Injection Analysis - Amal Saadoon Majeed; Ahmed Saleh Farhood; Luma Ahmed Mohammed Ali; Dakhil Nassir Taha (Indonesian Journal of Chemistry, 2017)
The research is included studying and designing micro flow injection system which is characterized with rapidity, simplicity, and low cost for the determination of green malachite dye. The study of flow rate of carrier stream, repeatability, dispersion coefficient, and calibration graph are conducted. It is found that the optimum conditions for the determination of mentioned dye are flow rate 4.200 mL/min, sampling rate 102 sample/h, limit of detection 0.05 ppm, linear range (0.05-18.00) ppm with linearity (R2=0.9700), RSD is 0.355, the repeatability for seven successive injections is studied for the two concentrations 5 ppm and 12 ppm, and the dispersion coefficient values are 1.73 and 1.28 at the two concentrations 2 ppm and 9 ppm respectively.